Microsoft Exchange 2013 cookbook: over 70 simple but incredibly effective recipes to take you through with the common tasks in Exchange 2013 - Horenbeeck, Michael Van; Tender, Peter De (Quick answers to common problems, 2013)
Exchange 2013 is much more than just a messaging platform. Because of the multitude of features both targeted at the end user as well as the platform’s administrator, deploying, migrating to or managing it might take just that little extra. Microsoft Exchange 2013 Cookbook is a practical, hands-on guide that will provide you with a number of clear, step-by-step exercises that help you to understand how the product works and how you should go about it in your own deployment. Throughout the book, you will be taken on a journey through the different aspects of Exchange 2013. We will look at the differences with previous versions and highlight how to configure and work with the product’s different features in a practical way. You will learn how to deploy, configure, and maintain Exchange 2013 from scratch or in an existing environment. We will walk you through different scenarios you’ll encounter in your day-to-day administration and explain how Exchange 2013 works. You will fundamentally understand what Exchange 2013 is all about and how to actually do things. You will learn all you need to know to successfully deploy (or migrate to) Exchange 2013 and maintain it once it’s been deployed.